Analisis Kelancaran Pengajuan Klaim BPJS Kasus Melahirkan di RS. X Kota Bengkulu - Nofri Heltiani; Lolli Nababan (Politeknik Negeri Jember, 2023)
The smoothness of submitting BPJS claims for childbirth cases is influenced by the accuracy of the code based on ICD-10 and ICD-9CM which refers to 3 categories namely complications of delivery, method of delivery and outcome of delivery, completeness of claim file requirements and completeness of documentation. Based on observations of 10 claim files for maternity cases submitted to BPJS, it was found that 6 (60%) files were pending due to diagnoses and codes entered on medical resumes not in accordance with BPJS, 1 (10%) did not have a doctor's signature, which resulted in delays the process of paying claims to hospitals that can cause material losses. The aim of the study was to find out the smoothness of submitting BPJS claims for childbirth cases at Hospital X Bengkulu City. This type of research is observational with a quantitative descriptive design. The population of this study is 137 files with a sample of 58 files taken by simple random sampling. The data used are primary and secondary data which were analyzed univariately using the frequency distribution. The results of the research are the accuracy of the case code giving birth to 36(62.1%) files, the completeness of the claim file requirements is 55(94.8%) files and the completeness of the documentation is 56(96.6%) files, but the claim files that fail to purify must be returned to hospital for repair. It is recommended that the hospital has an internal verifier as an evaluator before the file is sent to BPJS.